Formation at senior pupils of skills of self-educational musical activity (Pedagogy of Higher and Secondary Education, 2006)
In articles the problem of self-educational activity of schoolboys is examined during training to bases of music and a role of the teacher m her organization.
Keywords: piece of music; aesthetic education of schoolboys; organization ofindependent work